Accuracy of some EPBD implemented thermal performance calculation procedures - Silva, Pedro Correia Pereira da (2008)
The driving force of the thermal regulations revision in the European Union (EU) was the European Directive for the Energy Performance of Buildings – EPBD (European Commission, 2003). The main objectives of the EPBD are the harmonization of all thermal regulations in the EU and the optimization of buildings energy performance, taking into account the climatic conditions, indoor comfort conditions and economic viability, for both new and existing buildings. In order to be efficient and effective, the thermal regulations must lead to an accurate estimation of the energy performance of buildings allowing the energy certification to become a useful tool to compare results obtained in different countries. Having this fact in mind, the results obtained with the Portuguese calculation methodology, together with the results obtained with the methodologies used in two other countries (UK and Belgium), will be put side by side and also compared with the results obtained with a dynamic simulation tool for the energy performance estimation - VisualDOE. This case study will be based on the heating and cooling needs estimation of some Test Cells built in the School of Engineering of the University of Minho. The simulated results obtained using the simplified calculation models established in the mentioned three countries thermal regulations and by VisualDOE.